Physical and coordinative predictors of 50-m freestyle swimming performance among male students - Ahmad Yeri Sulistianto; Kamal Firdaus; Umar Umar; Nuridin Widya Pranoto (Global Econedu, 2026)
This study aimed to examine the direct and indirect effects of arm muscle strength, leg muscle explosive power, and hand–eye coordination on 50-m freestyle swimming speed among students of the Pandu Mahawira Swimming Guidance Program, Padang. This quantitative study employed a path analysis design involving 30 male students selected through purposive sampling. Data were collected using a hand grip dynamometer, Vertical Jump Test, Hand Wall Toss Test, and a 50-m freestyle swimming test. The data were analyzed using descriptive statistics and path analysis. Arm muscle strength contributed 24.20%, leg muscle explosive power 7.30%, and hand–eye coordination 6.40% to swimming speed. Through mediation by hand–eye coordination, the total contributions of arm muscle strength and leg muscle explosive power increased to 26.03% and 17.28%, respectively. Collectively, the predictors explained 77.8% of the variance in swimming performance. Arm muscle strength, leg muscle explosive power, and hand–eye coordination are significant determinants of 50-m freestyle swimming speed and should be developed simultaneously to optimize sprint swimming performance.